Interreligious hospitality: Reflections on death and eschatology. Issue 4 (5th December 2018) - Wirén, Jakob
Abstract: Is there an interreligious potential in the way we approach death and eschatology? Christian eschatology often suggests a unity that puts an end to religious otherness. It is difficult to find explicit, appreciative statements of any kind of otherness in many eschatologies. Given this situation, how can a Christian eschatology articulate hospitality and room for the religious Other as other? And what potential is there in the eschatological image of heavenly banquet?